MENINJAU DAMPAK TARIF PERDAGANGAN RI-TIONGKOK DALAM KOMPONEN NERACA PEMBAYARAN LUAR NEGERI - Cicih Ratnasih (Jurnal Manajemen FE-UB, 2015)
The purpose of this study o find out the process of rebalancing the balance of payments, due to the influence of the balance of payments is apparent in the process of rebalancing the balance of payments. By process of rebalancing the balance of payments consists of three components, namely the price level, exchange rate and monetary sectors. The increase in imports and decrease in exports of both together to encourage the reduction of payments surpluses this balancing process will run continuously with a surplus balance of payments of a country’s balance of payments coupled with derfisit foreign countries. The amount of money circulating in foreign countries will be reduced, then the price will drop and inflation, meaning the manufacturer increased competitiveness, increased exports and descreased imports of the foreign country. The exchange rate is for the devaluation and revaluation deficit to surplus. The success of devaluation to eliminate or reduce the imbalance depends on the elasticity of demand and supply of foreign exchange. Balance of payments imbalance is solely a monetary phenomenon, therefore controlling the amount of money circulating in the system of fixed exchange rates there will be no result. Affect the amount of money it will effectively be carried out in a free ecxhange rate system, in balancing the balance of payments.